What Do People Who Score Highly on the Tampa Scale of Kinesiophobia Really Believe? A Mixed Methods Investigation in People With Chronic Nonspecific Low Back Pain - Bunzli, S.; Smith, A.; Watkins, R.; Schütze, R.; O'Sullivan, Peter (Lippincott Williams and Wilkins, 2015)
Objectives: The Tampa Scale of Kinesiophobia (TSK) has been used to identify people with back pain who have high levels of "fear of movement" to direct them into fear reduction interventions. However, there is considerable debate as to what construct(s) the scale measures. Somatic Focus and Activity Avoidance subscales identified in factor analytic studies remain poorly defined. Using a mixed methods design, this study sought to understand the beliefs that underlie high scores on the TSK to better understand what construct(s) it measures. Methods: In-depth qualitative interviews with 36 adults with chronic nonspecific low back pain (average duration = 7 y), scoring highly on the TSK (average score = 47/68), were conducted. Following inductive analysis of transcripts, individuals were classified into groups on the basis of underlying beliefs. Associations between groups and itemized scores on the TSK and subscales were explored. Frequencies of response for each item were evaluated. Findings: Two main beliefs were identified: (1) The belief that painful activity will result in damage; and (2) The belief that painful activity will increase suffering and/or functional loss. The Somatic Focus subscale was able to discriminate between the 2 belief groups lending construct validity to the subscale. Ambiguous wording of the Activity Avoidance subscale may explain limitations in discriminate ability. Discussion: The TSK may be better described as a measure of the "beliefs that painful activity will result in damage and/or increased suffering and/or functional loss".